Analisis Kesalahan Simple Past Tense pada Latihan Menulis Recount Text pada Materi Kuliah Bahasa Inggris Dasar (Studi Kasus pada Kelas 63.1C.25 Jurusan Akuntansi Fakultas Ekonomi & Bisnis 2022/2023 UBSI) - Mursyid Kasmir Naserly (Departement of Mathematics Education, 2024)
This study investigated the misapplication of the simple past tense formula by 43 students who attended the Basic English course at the Department of Accounting, Faculty of Economics and Business, Bina Sarana Informatics University. The research data was obtained from the analysis of participants' recount text writing exercises to evaluate their ability to understand the formula. The research method applied is qualitative descriptive. Research findings show one common mistake that often arises, namely in the use of sentence elements that do not conform to the simple past tense formula. The error comes from students' negligence and lack of accuracy when completing assignments, as well as the tendency to mix past tense formulas with other tenses. Data collection is carried out through direct observation of student activities. The purpose of this study is to gain a deeper understanding of common mistakes in the application of simple past tense formulas, especially in the context of teaching basic English in a university environment.